Whither the Winds Blow: Philip’s Persian Policies, or the Lack Thereof - Sarakinski, Vojislav; Panovski, Stefan (Živa Antika, 2012)
The question of the “Persian policies” of Philip II is still disputed; the data from our extant sources does not indicate that the Macedonian king had active plans to invade Persia before solving the question of hegemony in Greece proper. The approximating political positions of Athens and Persia, as well as the desire for security in the immediate surroundings of the extended Macedonian kingdom, undoubtedly had some bearing on his decision. There is a reasonable amount of evidence that Philip kept the developments in Asia under close scrutiny; however, not a single extant source shows much more than that. One can speculate that Persia caught the king’s eye, for no other venture would offer such prospects for financial gain; furthermore, there was a real danger that Persia would draw near to some of the stronger Greek poleis, which would complicate the intricate political situation in Greece even further. It is practically certain that Philip had these things in mind; however, one is unable to determine whether these designs were clearly defined by 340 BC. The answer to the question whether Philip had (or, to begin with, whether he was aware that he should have) a Persian policy, depends on the connotation and weight that one chooses to assign to Isocrates’ Philippos. What stems from the whole lot is that, at this time, there were certain circles in Greece who were willing to entertain the thought of waging war against Persia. However, this does not imply that every Greek man of politics wished for such a development of events – but only that Isocrates, and several other members of his circle, dealt with the validity of a theoretical idea. No matter whether it happened in 346 BC, 340 BC, or only after the outcome of Chaeronea, there came a moment when the war against Persia was no longer just a possibility, but a reality. Philip's death stopped the largest enterprise in the history of the kingdom up to that time; its final stage was not achieved during his lifetime. The small amount of extant data prevents us from venturing into speculations about Philip’s intentions and final aims; however, it is fairly obvious that his endeavours do not imply a complete conquest of the Persian kingdom. If one wishes to make assumptions, it could be said that our sources indicate two things: that, as long as the Persians did not interfere in his endeavours in Thrace, Philip did not have clearly objectified ambitions in Asia; and that in no case did he show interest and ambition for the events beyond the Western satrapies. The extant data does not provide basis for speculation that Philip seriously thought about territories beyond Cilicia and Taurus, not to mention the entire territory of the Achaemenid kingdom.